Intenstinal helminth and protozoan parasites of pigs reared under intensive management system in Ibadan, Nigeria (2001)
Two hundred and seventy two pigs of different age groups reared in an intensive management system in 10 different locations in Ibadan were screened for intestinal helminth and protozoan parasites. The following incidences were recorded. Ascaris suum, 25.4% Oesophagostomuir. dentatus 13.6%, TricJiiiris suis, 10.7%; Strongylodes ransomi, 7.0%; Eimeria debliecki, 31.3%, Eimeria suis, 2.2% and Balantidium coli. 0.74%. Mixed infections with these parasites were common. No helminth egg was detected in all the piglets screened. The incidence of helminth parasites increased with age. So also was the worm burden. To prevent widespread infection with these parasites strict adherence to good management and hygiene in piggery pens is recommended